Christians, Muslims, and Mary: A History by Rita George-Tvrtković (American Journal of Islam and Society, 2020)
Rita George-Tvrtković's latest book explores the history of Mary's role in encounters between Christians and Muslims, focusing on her use by Christians in their assessments of Muslim faith and practice.To read the full book review, download the PDF file on the right.